Enhancing Smart Contract Security: A Machine Learning Framework Using Natural Language Processing and Unsupervised Techniques - Macovei, Andrei (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics